EYES WITH SUBRETINAL DRUSENOID DEPOSITS AND NO DRUSEN: Progression of Macular Findings. Issue 1 (January 2019) - Spaide, Richard F.; Yannuzzi, Lawrence; Freund, K. Bailey; Mullins, Robert; Stone, Edwin
Abstract : Purpose: To investigate the macular changes over time in eyes containing subretinal drusenoid deposits (also known as pseudodrusen) with no drusen >63 µ m. Methods: A consecutive series of patients were examined with color fundus photography, optical coherence tomography, and autofluorescence imaging with fluorescein angiography used as necessary. Exclusionary criteria included macular neovascularization, history of retinal surgery, pseudoxanthoma elasticum, and drusen >63 µ m. Results: There were 85 eyes of 54 patients. The mean age at baseline was 83.6 (±7.8) years, and there were 17 men. The mean follow-up was 5.0 (±2.9) years. At initial optical coherence tomography examination, 12 eyes had extrafoveal atrophy and 17 eyes had vitelliform deposits, which were yellowish white subretinal collections that showed intense hyperautofluorescence. During follow-up, 11 eyes lost vitelliform material. After the disappearance of small deposits, focal hyperpigmentation remained. Loss of larger deposits was associated with noteworthy sequela; six developed subfoveal atrophy and one macular neovascularization close to regressing vitelliform material. Subfoveal geographic atrophy developed in four other eyes without vitelliform material by extension from areas of extrafoveal atrophy. Macular neovascularization developed in seven eyes over follow-up. The CFH Y402H and ARMS2 A69S allele frequencies were 57% and 48.9%, respectively, which is similar to a group of age-related macular degeneration controls. One patient had a novel PRPH2 mutation, but did not have a vitelliform deposit; the remainder had a normal PRPH2 and BEST1 coding sequences. Conclusion: Eyes with subretinal drusenoid deposits and no drusen >63 mm have significant risk for the development of both neovascularization and geographic atrophy, the fundamental components of late age-related macular degeneration. An intermediate step in some eyes was the development of a vitelliform deposit, an entity not traditionally associated with age-related macular degeneration, but in these patients, the material seemed to be an important component of the disease pathophysiology. This vitelliform deposit was not associated with genetic markers for pattern dystrophy or Best disease. Abstract : Eyes with subretinal drusenoid deposits and no drusen have significant risk for the development of both neovascularization and geographic atrophy, the fundamental components of late age-related macular degeneration. An intermediate step in some eyes was the development of a vitelliform deposit, an entity not traditionally associated with age-related macular degeneration.